2020
DOI: 10.1016/j.conbuildmat.2020.120571
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical assessment of the shear behaviour of lime mortar clay brick masonry triplets

Abstract: This study investigates the fundamental shear response of masonry triplets incorporating fired-clay bricks and hydraulic lime mortars. It examines the behaviour under ambient-dry and wet conditions, corresponding to 48h submersion in water, as well as the effectiveness of strengthening with fibre reinforced polymer (FRP) laminates and glass fibre meshes (GFM). After describing the materials, mix designs and specimen details, the main results from 50 triplet tests subjected to shear and normal pre-compression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 72 publications
(94 reference statements)
2
7
0
Order By: Relevance
“…A recent complementary study carried out by the authors on triplets subjected to shear loading and varying levels of precompression, indicated that the initial shear strength was f v0 = 0.165 MPa for dry specimens and f v0 = 0.100 MPa for wet specimens (Bompa and Elghazouli 2020a). The triplets consisted of bricks which had identical properties to those from this paper, and the lime mortar had a strength similar to that in the WA-D and DA-D specimens.…”
Section: Shear-compression Failure Envelopessupporting
confidence: 52%
See 2 more Smart Citations
“…A recent complementary study carried out by the authors on triplets subjected to shear loading and varying levels of precompression, indicated that the initial shear strength was f v0 = 0.165 MPa for dry specimens and f v0 = 0.100 MPa for wet specimens (Bompa and Elghazouli 2020a). The triplets consisted of bricks which had identical properties to those from this paper, and the lime mortar had a strength similar to that in the WA-D and DA-D specimens.…”
Section: Shear-compression Failure Envelopessupporting
confidence: 52%
“…The brick tensile strength f bt can be obtained from tests or typically assumed as 10% of the compressive strength f b (CEN 2018). In the assessments undertaken in this paper, the shear sliding parameters were determined based on previous test data (Bompa and Elghazouli 2020a), and by using the ranges illustrated in Fig. 13 and described before.…”
Section: Stiffness and Strength Of Large Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, all of the mortar triplets exhibited minor values of shear stress, below 0.11 MPa. In other experimental results, when lime mortar was used, it had a low triplet shear strength value [30,[48][49][50]. Two types of failure mode were observed: (1) detachment of the mortar bed joint and bricks, and (2) detachment of the mortar layer.…”
Section: Shear Strength Of Masonry Tripletsmentioning
confidence: 84%
“…The diagonal shear and sliding strength of URM is greatly dependent on the mortar-brick interaction. In general, the interface mortar-brick shear response greatly depends on the moisture content, porosity, mortar strength, and conditioning type (Mazzotti et al 2014;Bompa and Elghazouli 2020a), with saturation causing a deterioration in strength and stiffness (Franzoni et al 2015;Bompa and Elghazouli 2020b).…”
Section: Introductionmentioning
confidence: 99%